THE FEMININE AND MASCULINE ARCHETYPES IN THE STRUCTURE OF A PAGON MYTH - Tetiana A. Kuptsova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The aim of the article is to reveal peculiarities of the formation of feminine and masculine archetypes in a pagon myth; to substantiate, how male and female bodies change into archetypes; to analyze peculiarities of the archetypes' influence on stereotype formation in the mythological consciousness of our ancestors. Methods and approaches. To understand gender symbolical and imaginative sphere of culture of great importance is K. G. Yung's theory of archetypes. Historical and philosophical understanding of theoretic gender representation is possible owing to methods of feminist cultural criticism. To investigate specific features of archetypes' influence on the gender stereotype formation in mythological consciousness of our ancestors the theory of ethnoarchetype developed by V. F. Yatchenko is also valuable. Scientific novelty. It is proved, that the mythological consciousness of Ukrainian ancestors and their archetypes had no strictly fixed social status. The transformation into patriarchal male and female stereotypes was influenced by the essentialistic establishments which defined man's social role as a leading one and a woman's one as of minor importance. The social and cultural secondary role of woman was softened by female mystic charisma, based on the ability to give birth and to be mother of every living being. In the Ukrainian culture this role was embodied in the sacral archetype of the Mother-Land, which led to complimentary attitude of national philosophy to feminine concept. With the help of historical, philosophical and gender scientific methods the original material was analysed, which helped to discover the particularities of gender stereotypes influence on the formation of vision in the Ukrainian philosophy. Conclusion. The analysis given in this article proves that the archetypes of Anima and Animus as sensually perceived culture – ontological transcendent reality, being psychological immanent reality, were reflections of the objectively existing structures of being, combination of real and ideal, space and mental. In the structure of the mythological consciousness they existed as unperceived but determinant factors of the material world praphenomenon of being. They often produce their influence on the modern cultural life of Ukrainian people in the forms of stereotype notions about the feminine and masculine concepts.